Periodic collisions between the moon Prometheus and Saturn's F ring - Murray, C. D.; Winter, SMG (Macmillan Magazines Ltd, 1996)
Saturn's F ring, which lies 3,400 km beyond the edge of the main ring system, was discovered by the Pioneer 11 spacecraft(1) in 1979. It is a narrow, eccentric ring which shows an unusual 'braided' appearance in several Voyager 1 images' obtained in 1980, although it appears more regular in images from Voyager 2 obtained nine months later(3). The discovery of the moons Pandora and Prometheus orbiting on either side of the ring provided a partial explanation for some of the observed features(4). Recent observations of Prometheus(5,6) by the Hubble Space Telescope show, surprisingly, that it is lagging behind its expected position by similar to 20 degrees. By modelling the dynamical evolution of the entire Prometheus-F ring-Pandora system, we show here that Prometheus probably encountered the core of the F ring in 1994 and that it may still be entering parts of the ring once per orbit. Collisions with objects in the F ring provide a plausible explanation for the observed lag and imply that the mass of the F ring is probably less than 25% that of Prometheus.